COVID-19 pandemic impact on United States intimate partner violence organizations: administrator perspectives - Randell, Kimberly A. (Journal of family violence, 2025)
Purpose: The COVID-19 pandemic has increased challenges to intimate partner violence (IPV) service provision. This study aimed to explore administrative perspectives on the impacts of the COVID-19 pandemic on United States regional and national IPV service organizations. Methods: We interviewed 35 administrators working within state, regional, or national organizations addressing IPV. Interview domains included (1) organizational response to COVID-19, including communication and supporting employees and partner agencies, (2) impact on marginalized communities, and (3) resource needs. We used a hybrid deductive-inductive approach and thematic analysis for coding and analysis. Results: We identified four key themes: (1) COVID-19 worsened pre-existing challenges and created new challenges at multiple levels within IPV service organizations; (2) IPV service organizations initiated multi-level initiatives to support IPV survivors, their staff, their organization, and their member/partner agencies; (3) Organizations identified changes that should continue beyond the pandemic; and (4) Systemic racism compounded the impact of COVID-19 on IPV survivors and IPV service agencies. Conclusions: Findings suggest that (1) multi-level responses are needed for robust support of IPV survivors during and beyond the pandemic and (2) a syndemic model that addresses underlying structural inequities may strengthen efforts to support IPV survivors during a pandemic or other large-scale disaster.